2020
DOI: 10.1002/ceat.201900452
|View full text |Cite
|
Sign up to set email alerts
|

Biohydrogen Production Through Dark Fermentation

Abstract: Waste organic biomass is regarded as the most suitable renewable source for conversion to produce biofuels and biochemicals. Owing to its high‐energy potential and abundancy, lignocellulosic biomass can be utilized to produce alternative energy in the form of gaseous and liquid biofuels. Microbial conversion of waste biomass is the most successful technology for the generation of biohydrogen through dark fermentation. Different biological hydrogen production technologies along with process parameters are descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(45 citation statements)
references
References 147 publications
(134 reference statements)
0
36
0
Order By: Relevance
“…The thermochemical processes use heat and chemical reactions to transform biomass into energy or energy carriers while microorganisms and enzymes are used in the biological processes [9][10][11]. Several studies have reported the thermochemical and biological conversion of biomass to energy or energy carriers [12][13][14][15]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The thermochemical processes use heat and chemical reactions to transform biomass into energy or energy carriers while microorganisms and enzymes are used in the biological processes [9][10][11]. Several studies have reported the thermochemical and biological conversion of biomass to energy or energy carriers [12][13][14][15]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen generation via fermentation is more suitable for the production of cleaner energy and the more efficient treatment of organic waste. Waste organic biomass is considered as the most appropriate renewable source for conversion to produce biofuels due to its high energy potential and abundancy (Sarangi and Nanda, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth highlighting why waste diapers (WD) are attractive for biohydrogen production. Among the merits and benefits of this use of WD we can cite the following: (i) the WD have a high content of cellulose (40% db); earlier research has demonstrated that substrates and wastes rich in cellulose and hemicellulose or carbohydrates can produce an attractive amount of biological hydrogen (Rodríguez-Valderrama et al, 2020;Alvarez et al, 2020;Sarangi and Nanda, 2020;Solowski et al, 2020;Weide et al, 2019;Catalán and Sánchez, 2019;Yeshanew et al, 2018;Roy 2017;Robledo-Narváez et al, 2013). Thus, in principle, the potential of biohydrogen production of WD, could be very high.…”
Section: Introductionmentioning
confidence: 99%
“…If successful, DF of the OFWD would hold promise for integration to biorefineries from wastes that could co-ferment this waste with a variety of agricultural and agroindustrial wastes of similar characteristics (cellulosic and lignocellulosic wastes, i.e., food and textile wastes) (Rodríguez-Valderrama et al, 2020;Sarangi and Nanda, 2020;Solowski et al, 2020;Weide et al, 2019;Catalán and Sánchez, 2019;Yeshanew et al, 2018;Roy 2017;Robledo-Narváez et al, 2013). As it was hinted above, biological hydrogen production can be easily incorporated to several biorefinery platforms as a first stage of biofuel generation, followed by a network of processes devoted to obtaining value-added products and possibly more energy (Poggi-Varaldo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%